(untitled) (Journal of Forensic Medicine & Toxicology, 2018)
In cases of mass disaster non availability of complete skeletal remains problem arise for identification of individuals which can be partially done by reestablishment of stature from various bony frameworks available to us at the said time. In our study we have taken 400 people population comprising each half of male and female of age group 20 to 25 years resident of Malwa region of Punjab for the same tibial length is recorded using standard measurement technique multiplication factor and linear regression equation were calculated using above mentioned variables.